TRIM56-mediated monoubiquitination of cGAS for cytosolic DNA sensing - Gil Ju Seo (Nature Portfolio, 2018)
The protein cGAS responds to the presence of cytosolic DNA by producing the second messenger cGAMP, which triggers antiviral interferon responses. Here, Seo et al. show that ubiquitination by the E3 ligase TRIM56 enhances cGAS activity and is important for the immune response against DNA viruses.